ROS‐Driven Nanoventilator for MRSA‐Induced Acute Lung Injury Treatment via In Situ Oxygen Supply, Anti‐Inflammation and Immunomodulation - Zheng Luo; Qi Wang; Xiaotong Fan; Xue Qi Koh; Xian Jun Loh; Caisheng Wu; Zibiao Li; Yun‐Long Wu (Advanced Science)
Abstract Hypoxia, inflammatory response and pathogen (bacterial or viral) infection are the three main factors that lead to death in patients with acute lung injury (ALI). Among them, hypoxia activates the expression of HIF‐1α, further exacerbating the production of ROS and inflammatory response. Currently, anti‐inflammatory and pathogen elimination treatment strategies have effectively alleviated infectious pneumonia, but improving lung hypoxia still faces challenges. Here, a vancomycin‐loaded nanoventilator (SCVN) containing superoxide dismutase (SOD) and catalase (CAT) is developed, which is prepared by encapsulating SOD, CAT and vancomycin into a nanocapsule by in situ polymerization. This nanocapsule can effectively improve the stability and loading rate of enzymes, and enhance their enzyme cascade efficiency, thereby efficiently consuming •O2− and H2O2 to generate O2 in situ and reducing ROS level. More interestingly, in situ O2 supply can effectively relieve lung hypoxia to reduce HIF‐1α expression and balance the number of M1/M2 macrophages to reduce the levels of TNF‐α, IL‐1β and IL‐6, thereby alleviating the inflammatory response. Meanwhile, vancomycin can target and kill MRSA, fundamentally solving the cause of pneumonia. This nanoventilator with antibacterial, anti‐inflammatory, ROS scavenging and in situ O2 supply functions will provide a universal clinical treatment strategy for ALI caused by pathogens.